The reality of technology valleys as a policy for financing Saudi universities and their activation proposals in the light of the American Silicon Valley experience - Sanior, Ameena Ali (Journal of Educational and Psychological Sciences, 2023)
The study aimed to address the reality of technical valleys as a policy for funding Saudi universities and proposals to activate them in the light of the American Silicon Valley experience. To achieve this goal, the analytical descriptive approach was used. The study used an interview with ten faculty members to collect data. The study included a general framework, then six axes. The first axis presented the conceptual framework for financing university education, the second axis dealt with the reality of financing university education in the Kingdom of Saudi Arabia, the third axis revealed the reality of technology valleys as a policy for financing university education in the Kingdom of Saudi Arabia, and the fourth axis presented the features of the American Silicon Valley experience in financing university education. The fifth axis identified the obstacles to activating the technology valleys as a policy for financing university education in the Kingdom of Saudi Arabia, and the sixth axis presented proposals for activating the technology valleys as a policy for financing university education in the Kingdom of Saudi Arabia in the light of the American Silicon Valley experience, including the reproduction of advanced technological universities by Saudi universities to keep pace with technological change, the development of modern policies To increase the effectiveness of technical valleys f In universities, through: providing the appropriate geopolitical environment for the growth of various businesses, strengthening the relationship between investment banks and universities to provide financing sources and bank loans, and linking government support to private companies with their participation in technology valleys and supporting projects in them. Imposing a policy of community participation for local capital owners, developing measurement and evaluation indicators to know the reference level, providing empowerment by setting economic policies that facilitate the knowledge economy, establishing projects, financing and marketing products.
Keywords: technical valleys; Saudi universities; community participation